Problemas Resueltos - Razonamiento matemático
Problema 115
Sean \( \vec{a} = (3, -1) \) y \( \vec{b} = (-5, \, 3) \); luego el vector \( \vec{c} \), tal que \( \vec{a} + \vec{b} - 2\vec{c} = \vec{0} \) es el siguiente:
-
\( (-2, \, 2) \)
-
\( (2, - 2) \)
-
\( (1, \, 1) \)
-
\( (1, -1) \)
-
\( (-1, \, 1) \)
Intenta resolverlo antes de ver la respuesta...
-
\( (-1, \, 1) \)
En efecto:
\[
\begin{aligned}
\vec{a} + \vec{b} – 2 \vec{c} = \vec{0}
&\Rightarrow
\vec{a} + \vec{b} = 2\vec{c}
\\[1em]
&\Rightarrow
2 \vec{c} = \vec{a} + \vec{b}
\\[1em]
&\Rightarrow
2 ( c_1 , \, c_2 ) = (3, -1) + (-5, \, 3)
\\[1em]
&\Rightarrow
( 2 c_1, \, 2c_2 ) = ( 3-5, -1 + 3 )
\\[1em]
&\Rightarrow
( 2c_1, \, 2c_2 ) = (-2, \, 2)
\\[1em]
&\Rightarrow
2c_1 = -2 \quad \text{ y } \quad 2c_2 = 2
\\[1em]
&\Rightarrow
c_1 = -1 \quad \text{ y } \quad c_2 = 1
\\[1em]
&\Rightarrow
\boldsymbol{ \vec{c} = (c_1, \, c_2) = (-1, \, 1) }
\end{aligned}
\]
\[
\begin{aligned}
&\vec{a} + \vec{b} – 2 \vec{c} = \vec{0}
\\[1em]
&\hspace{1em}\Rightarrow
\vec{a} + \vec{b} = 2\vec{c}
\\[1em]
&\hspace{1em}\Rightarrow
2 \vec{c} = \vec{a} + \vec{b}
\\[1em]
&\hspace{1em}\Rightarrow
2 ( c_1 , \, c_2 ) = (3, -1) + (-5, \, 3)
\\[1em]
&\hspace{1em}\Rightarrow
( 2 c_1, \, 2c_2 ) = ( 3-5, -1 + 3 )
\\[1em]
&\hspace{1em}\Rightarrow
( 2c_1, \, 2c_2 ) = (-2, \, 2)
\\[1em]
&\hspace{1em}\Rightarrow
2c_1 = -2 \quad \text{ y } \quad 2c_2 = 2
\\[1em]
&\hspace{1em}\Rightarrow
c_1 = -1 \quad \text{ y } \quad c_2 = 1
\\[1em]
&\hspace{1em}\Rightarrow
\boldsymbol{ \vec{c} = (c_1, \, c_2) = (-1, \, 1) }
\end{aligned}
\]